Greek lives - Pelling, C (International Plutarch Society, 2004)
This was the text of my inaugural lecture, and the editors of Ploutarchos were kind enough to suggest to me that, given its Plutarchan emphasis, it might have interest to a wider public. They also, even more kindly, suggested it would be best in its original oral form, including the local pleasantries and some references - for instance to the party which followed - which are extremely occasion-specific. I hope that the informality of style will indeed convey something of the flavour of the occasion. It was also marked by a momentary failure of electricity half way through, plunging the audience of some 200 people into darkness. Plutarchans may take some malicious pleasure that this happened exactly on the word 'Nepos'.